Situated Feminisms, Art, and New Technologies: A Study of the Aesthetic Technological Experiences of the Women's Movement in Argentina (2013-2017) (London Journal of Research In Humanities and Social Sciences, 2025)
Women have forged a dense relationship between politics and the creative intervention of public space. They've enabled new meanings and significations through diverse artistic practices aimed at denouncing violence and the conditions of women's inequality within contemporary capitalism. These experiences have not only been formulated, thought through, and executed by women who self-identify as artists or communicators, but also by those who have learned to inhabit the political body in a counter-hegemonic way. What's also called into question is the conception of canonized art, which relates to social events and takes forms differentiated from the traditional: installations (with applied technology or Artificial Intelligence), performances, sound poetry, contemporary dance, video art, among others (Cippollini, 2003). The intersections of art, technology, and politics are grounded in a feminist and disruptive reading of public intervention, not only as a possible stage but also in relation to bodily dissidences, images (e.g., the case of "Guerrilla Girls"), sounds, and words (Oliveras, 2011). In this triad, a new problem emerges related to the invisibilization of women's marginal place in certain artistic branches. In this new transnational identity constitution (Bidaseca, 2011), cyborg (Haraway, 1995), and framed in terms of potentiality (Butler, 2015), new conditions of possibility are established for those desiring bodies to inhabit their territories, intervene in them, produce common, egalitarian meanings, and fight for rights within the very system of inequalities. A historical genealogical journey through Argentine feminisms (Bilbao, 2017 and 2019) allows for an understanding of other dimensions of the dominant conditions over practices and knowledge linked to art, technology, and communication. The so-called popular feminisms, connected to artistic practice, enter this threshold of new significations regarding the potentialities of differentiated bodies due to their class, gender, or ethnicity. Understanding the potentialities of an emancipatory movement in a particular historical moment shows why it constitutes an event (Lazzarato, 2006). From this, the paradigmatic singularities of creative strategies and aesthetic configurations linked to new technologies, contributed by feminisms situated around the various historical contingencies of women, emerge. The relations between gender studies, art, and politics in Argentina have a long and intense theoretical corpus and literature problematizing specific moments in social history, establishing particular links between these fields (Giunta, 2010, 2014; Gutirrez, 2008;